2009
DOI: 10.1111/j.1750-3841.2009.01061.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of Fresh‐Cut Apples, Pears, and Melons Using Natural Additives

Abstract: Improving the quality of different fresh-cut fruits by adding natural substances was studied. "Fuji" apples, "Flor de Invierno" pears, and "Piel de Sapo" melons were treated with calcium lactate, N-acetyl-L-cysteine, glutathione, and malic acid and stored for 4 wk at 4 degrees C. Instrumental texture (penetration), microstructure (light microscopy), acidity, soluble solids, color, pectinmethylesterase activity, and microflora were studied. The results showed that the combined treatment reinforced the cell wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Citric acid (CA) is often used in conjunction with AA to maintain product color, due to its ability to reduce pH, therefore decreasing PPO activity, and for its metal chelating ability that limits the availability of ions required for PPO activation (Abbott et al., 2004; Huque et al., 2013). The consumers wish to reduce or eliminate the chemically synthesized additives in food has led to the interest of using natural compounds (Alandes et al., 2009). “Mate” is a traditional drink widely consumed in Uruguay, Argentina, Brazil, and Paraguay, which consists of an infusion of the milled dried leaves of Ilex paraguariensis St.…”
Section: Introductionmentioning
confidence: 99%
“…Citric acid (CA) is often used in conjunction with AA to maintain product color, due to its ability to reduce pH, therefore decreasing PPO activity, and for its metal chelating ability that limits the availability of ions required for PPO activation (Abbott et al., 2004; Huque et al., 2013). The consumers wish to reduce or eliminate the chemically synthesized additives in food has led to the interest of using natural compounds (Alandes et al., 2009). “Mate” is a traditional drink widely consumed in Uruguay, Argentina, Brazil, and Paraguay, which consists of an infusion of the milled dried leaves of Ilex paraguariensis St.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of overall browning in the FWN during 24 h storage was positively correlated with PPO activity by kinetic studies [ 5 ]. Alandes reported that L-cysteine could reduce the PPO activity and inhibit browning in fresh apples [ 30 ]. It was concluded that the inhibitory effect of L-cysteine on the browning of FWN was achieved by reducing the pH and PPO activity.…”
Section: Resultsmentioning
confidence: 99%
“…Fresh-cut is currently a growing market because of its convenience, and availability (Alandes et al, 2009;Zsivanovits et al, 2018). Demand for fresh-cut vegetables is continuously increasing.…”
Section: Introductionmentioning
confidence: 99%